Dividends Policy, Retained Earnings and Share Prices Applied Study of Iraqi Stock Market - Shaker Sultan, Ayad (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Despite the abundance of research in the field of dividend policy and share price, but still it remains a puzzle which whether dividend policy affects the share price or not. This study attempts to empirically investigate the relationship between dividends, retained earnings and share prices. As it is well known that the main objective of corporation should be to maximize the value of the firm, as the value, price, of the firm`s common share depends on the policies that the management adopt about dividends and internal financing decisions. The study relies on secondary data, which was collected for a period of ten years (2005-2014) from the audited annual financial reports of four-companies sample of different industries that are listed in Iraqi`s stock. The firms included in the sample have many consecutive years of dividend payments and also have earnings information for the ten years mentioned. The study concluded that dividend policy is of a great importance because it affects the value of the company, as well as attracting the attention of external and internal users of accounting information; the study finds out that dividend per share (DPS) and dividend pay-out policy are related to return on equity (ROE). Meanwhile, earning per share (EPS) is negatively behaving with (DPS) and dividend pay-out ratio (DPR). Therefore, the study may advise the concerned firms to well-studied financial planning and policy so as to enhance their performance and efficiency.